2022
DOI: 10.1186/s12884-022-04725-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum vitamin D status with gestational diabetes mellitus and other laboratory parameters in early pregnant women

Abstract: Background The association between serum 25-hydroxy vitamin D (25(OH)D) status and gestational diabetes mellitus (GDM) gained attention in recent years, however the conclusion is still controversial due to many interfering factors, such as region of living, environment, lifestyle, and food supplements. Other metabolites (laboratory parameters) are also important in reflecting gestational states. This study aimed to investigate the association of serum 25(OH)D status in early pregnancy with GDM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…There are conflicting reports exist regarding the association between vitamin D levels during early pregnancy and the development of GDM. Some studies have figured out that vitamin D deficiency during early pregnancy is associated with an increased risk of GDM [ 7 , 8 , 28 30 ], while other studies have not supported this association [ 31 – 33 ]. A systematic review and meta‑analysis consisting of 37,838 pregnant women concluded that lower levels of vitamin D in early pregnancy were associated with a higher risk of developing GDM.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports exist regarding the association between vitamin D levels during early pregnancy and the development of GDM. Some studies have figured out that vitamin D deficiency during early pregnancy is associated with an increased risk of GDM [ 7 , 8 , 28 30 ], while other studies have not supported this association [ 31 – 33 ]. A systematic review and meta‑analysis consisting of 37,838 pregnant women concluded that lower levels of vitamin D in early pregnancy were associated with a higher risk of developing GDM.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Along with the major role of vitamin D in the metabolisms of calcium and phosphorus, some nonspecific roles of vitamin D have also been in the body such that, the deficiency of vitamin D will lead to metabolic syndromes, cardiovascular disease, immunocompromisation, and depression. [ 7 8 ] Because of the presence of vitamin D receptors in the female reproductive system, including the uterus, endometrium, ovaries, and placenta, the possible role of this vitamin in female reproduction has been suggested. [ 9 ] It has been reported that vitamin D deficiency is associated with gestational diabetes, endometriosis, polycystic ovary syndrome, preterm labor, and preeclampsia.…”
Section: Introductionmentioning
confidence: 99%